Reinterpretasi Jilbab dan Aurat Perempuan dalam Al-Qur’an Menurut Perspektif Ulama Kontemporer - Masyhur, Laila Sari (PT. Banjarese Pacific Indonesia, 2024)
This article examines the views of classical and modern scholars on what is related to jilbab. It's a matter of culture. That's more of a moral expression. Nevertheless, this expression invites other meanings that need to be associated according to necessity. This need may be hard to guess, so whatever it means is hidden behind the text. (the hidden texts). Thus, it is perfectly logical that the jellyfish are categorized in the sphere of culture. However, not a few scholars have viewed the figs in the colors of the sacrament, and these sacred values have been regulated according to normative principles. This article will show the diversity of the views of classical and contemporary scholars in understanding the Qur'an as the texts of the Islamic source law relating to the jilbab.